(untitled) (Bangladesh Journal of Botany, 2021)
Individual and interaction effects of plant growth regulators and fertigation on quality of pomegranate were investigated. Maximum mean polar diameter (9.59 cm), equatorial diameter (8.10 cm), fruit weight (206.06 g),fruit volume (190.86 cc), number of arils per fruit (416.81), aril weight per fruit (146.35 g), weight of 100 arils (35.86 g) and aril per cent (70.92 %) along with minimum specific gravity (1.090), rind thickness (5.15 mm), rind per cent (29.09%) and fruit cracking (5.58%) were recorded in F2 (100 per cent RDF through fertigation). Similarly, spray of 100 ppm NAA (N2) and 250 ppm ethrel (E2) significantly influenced the above characteristics of fruit. Treatment combination of 100 ppm NAA + 150 ppm ethrel + 100% RDF through fertigation (N2E1F2) gave better quality fruit over other treatments including control. Bangladesh J. Bot. 50(3): 623-631, 2021 (September)